Development of Microsite-Based Learning Media on the Schorodinger Equation to Improve Students' Critical Thinking Skills - Proki Karandja Hawur; Jayanti Kharisma Putri; Pratama Fahri Asidiq; Rida SN Mahmudah (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2025)
Critical thinking skills are essential for students' success in modern education. This study focuses on the development of microsite-based learning media to improve students' critical thinking skills, especially in understanding the Schrödinger equation. The focus of this study is the important role of critical thinking in modern education and the problems faced by Indonesian students when they learn with a rote approach from traditional learning. The research problem shows that innovative and creative learning methods are needed to improve critical thinking skills. The solution to this problem is to create a Schrödinger equation microsite. The methodology used is Research and Development (R&D) using the 4D development model consisting of Define, Design, Develop, and Disseminate. The results show that the microsite-based learning media is valid and practical, as evidenced by expert validation and positive student comments. Overall, the microsite learning media is considered feasible and useful for students to use in class, and shows the possibility of additional improvements depending on input for wider implementation. Implementation with a group of students shows that the Schrödinger equation microsite is effective.